Mechanical properties and toughening mechanism of TiB2/NiTi reinforced titanium matrix composite coating by laser cladding. (5th September 2015) - Lin, Yinghua; Lei, Yongping; Fu, Hanguang; Lin, Jian
Graphical abstract: Highlights: Coarse TiB2 and the network-like structure can be formed during laser cladding. The micro-hardness can be improved through reinforcement of coarse TiB2 . The fracture toughness can be improved through crack deflection and bifurcation. Abstract: Coarse TiB2, fine TiB and NiTi/NiTi2 reinforced titanium matrix composite coatings with part of the network-like structure reinforcement distribution were prepared by laser cladding on Ti–6Al–4V alloy using premixed Ni, coarse TiB2, fine TiB2 and Ti powder. The amount and the size of coarse TiB2 were decreased with increasing distance from the surface. The network-like structure was mainly consisted of NiTi and Ni3 Ti, and the characteristic of network-like structure gradually became clearer from the top to the bottom. The micro-hardness of the coating was first decreased abruptly and then decreased gradually with increasing distance from the surface, but fracture toughness of the coating was first decreased and then increased. The fracture toughness of the coating can be improved through the crack deflection and the bifurcation, but the crack deflection and the bifurcation were random.